(untitled) (Journal of Electronics Technology Exploration, 2026)
The demand for energy-efficient computing systems is growing as workloads on embedded devices, edge computing, and scientific computing continue to expand. In this context, a comparison between the ARM and RISC-V architectures is important because both are widely used in System-on-Chip (SoC) designs but have different performance and energy efficiency characteristics. This article presents a comparative review of various benchmark studies on the Odroid XU4, Rock960, and Nezha D1 platforms using the NAS Benchmark, TensorFlow Lite Benchmark, and OpenFOAM. The summarized results show that RISC-V implementations generally have lower average power consumption but do not always yield a better performance-per-watt ratio. For some workloads, ARM platforms still demonstrate superior throughput and energy efficiency, while RISC-V performance is heavily influenced by the number of cores, accelerator support, and the maturity of the software ecosystem. Therefore, ARM remains more competitive for high-performance workloads, whereas RISC-V remains promising for power-efficient applications and continues to evolve.